Studi kasus dampak pinjaman online pada perilaku konsumen dan gaya hidup - Grace Putlia; Hary S. Sundoro; Fildzah Shobrina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
The impact of digitalization on the financial sector has made it easier for people to carry out various financial transactions, including online loans (pinjol). The echo of the use of legal pinjol registered with the OJK has not stopped until 2024. The reason is that illegal pinjol continues to emerge in society. In the field, many cases of violence and suicide were found due to online loans. Based on the existing phenomenon, the purpose of this study was first to review in more depth the understanding of the people of Tangerang City about the impact of online loans and secondly, the understanding of the people of Tangerang City about the impact of online loans on consumer behavior and lifestyle. This study uses a qualitative case study design because the research problem concerns a phenomenon. 10 people were selected as the research sample, meeting the specified criteria. The study's results show that, in general, the people of Tangerang City's understanding of the impact of online loans remains limited.